Attitudes to depression in Saudi Arabia: a preliminary study. Issue 3 (2nd July 2016) - Alrahili, Nader; Almatham, Fahad; Bin Haamed, Haifa; Ghaziuddin, Mohammad
ABSTRACT: Depression is la common illness, affecting about 10% of the population. Although it is a global condition, its awareness is limited in developing countries. This study examines the attitudes to depression in a sample of men and women in Saudi Arabia, a major country in the Middle East with a population of about 21 million. A random sample of subjects ( n = 137; 80 male and 57 female) completed a questionnaire on mental health and depression. Questions explored the attitudes and beliefs of the respondents about the causes and treatment of depression. Responses were categorized into three groups: 'yes', 'no' and 'do not know'. The results showed that although an overwhelming number of respondents (87%) believed that depression was a medical illness, 75% said that depression would not occur if 'one was close to God' and more than half (57.66%) blamed 'black magic' or the 'evil eye'. While 83.94% believed that treatment could improve its symptoms, 45.98% thought that antidepressants caused addiction. Thus, while most subjects believed that depression could be caused by supernatural factors, they also believed that it was an illness requiring treatment. These findings underscore the importance of including cultural/religious strategies in the treatment of depression.